2014
DOI: 10.1371/journal.pone.0104527
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Regeneration Using Strontium-Loaded Mesoporous Bioactive Glass Scaffolds in Osteoporotic Rats

Abstract: Recent studies demonstrate that the rate of periodontal breakdown significantly increased in patients compromised from both periodontal disease and osteoporosis. One pharmacological agent used for their treatment is strontium renalate due to its simultaneous ability to increase bone formation and halt bone resorption. The aim of the present study was to achieve periodontal regeneration of strontium-incorporated mesoporous bioactive glass (Sr-MBG) scaffolds in an osteoporotic animal model carried out by bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…In the multilayer formation stage or the early stage, the expression of cell cycle or growth‐related genes increase, and in the late stage, matrix maturation and early mineralization occur. Altogether, the effects of Sr 2+ on osteogenic differentiation of hPDLCs supported a role for Sr 2+ in osteoblastogenesis and bone repair and was consistent with our previous study . Indeed, a great deal of preclinical and clinical studies provided evidence that Sr 2+ ‐mediated activation of multiple signaling pathways resulted in the regulation of genes promoting the osteoblastic differentiation …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the multilayer formation stage or the early stage, the expression of cell cycle or growth‐related genes increase, and in the late stage, matrix maturation and early mineralization occur. Altogether, the effects of Sr 2+ on osteogenic differentiation of hPDLCs supported a role for Sr 2+ in osteoblastogenesis and bone repair and was consistent with our previous study . Indeed, a great deal of preclinical and clinical studies provided evidence that Sr 2+ ‐mediated activation of multiple signaling pathways resulted in the regulation of genes promoting the osteoblastic differentiation …”
Section: Discussionsupporting
confidence: 90%
“…Karakan et al found that Sr 2+ could prevent the alveolar bone loss in experimental periodontitis. Our previous studies also suggested that biomaterial modified with Sr 2+ could significantly stimulate the osteogenesis/cementogenesis‐related gene expression of hPDLCs and provide a more significant periodontal regeneration in the osteoporotic animal model …”
Section: Introductionmentioning
confidence: 88%
“…When incorporated within mesoporous bioactive glass scaffolds, Sr stimulated osteoblastic proliferation and differentiation of MSCs and osteoblastic cells [167,168]. Furthermore, in vivo increased bone formation was enhanced by Sr ions released from the mesoporous bioactive glasses scaffolds [168][169][170] and Ca phosphate scaffolds [171]. Recently, Sr-substituted bioactive glassincorporated PCL nanofibers were developed [172].…”
Section: Control Of Therapeutic Ionsmentioning
confidence: 99%
“…It has been reported that strontium preferentially stimulates cell proliferation of mesenchymal and osteoblastic cells (10,34) and, because of the osteoblast-like characteristics of the PDL cells, we may consider it an elective factor to be used in PDL regenerative therapy. Literature reports the effects of strontium in PDL regeneration, demonstrating its ability to promote proliferation and osteogenic differentiation of PDLSCs (11,12,35,36), but in these studies they have tested few and different concentrations of strontium and examined only a single process at once. Therefore, our purpose was to assess whether and in which way the same concentrations of SrCl2 (from 0.5 to 500 μg/ml) may influence both of the proliferation activity and the mineralization process of PDLSCs.…”
Section: Discussionmentioning
confidence: 99%